THE IMPORTANCE OF ACTUALIZING THE EXISTENCE OF DIRECTING ELEMENTS IN THE REGIONAL DISASTER MANAGEMENT AGENCY ACCORDING TO LAW NUMBER 24 OF 2007 IN ASAHAN DISTRICT - Emmi Rahmiwita Nasution; Evi Purnamawati; Zulfahri Harahap (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
The Steering Element in the Regional Disaster Management Agency (BPBD) is an important organ that must exist, where one of its tasks is to provide input in the form of suggestions to the BPBD Leadership as a derivative of the National Disaster Management Agency (BNPB) in the regions. The absence of a Directing Element organ in BPBD will have no impact walking BPBD functions optimally and violates existing provisions. The existence of a Steering Element is very important, where the input provided is related to strategies, plans and evaluations at BPBD, where the Steering Element consists of employees from Government Agencies and those from Professional/Expert Societies. Empirical research is used due to the potential gap between Das Sollen and Sein , namely there is a gap between existing regulations and the existing situation. The type of field research referred to is obtaining data from research field directly which is the result become objective from research This that is Having a Steering Element in BPBD Asahan is an important and urgent matter. The result form found there are obstacles in implementation is one of them because mechanism the determination is assessed eat time so that needed seriousness as well as support budget from since start of the registration process until financing in implementation his job. The conclusion is that the existence of a Steering Element in the BPBD in Asahan is important and immediate actualization and existence This steering element must also be complemented by legal regulations at the level Regional District .